Structural Changes of the 21st Century and their Impact on the Gold Price - Grynberg, Roman; Kaulihowa, Teresa; Singogo, Fwasa K (Journal of Economics and Behavioral Studies, 2019)
Beginning in the trough of 2000 and culminating in the peak of 2012, gold prices have exhibited a spectacular and unparalleled increase. Based on annual averages, the price of gold did not decrease at all over this 12 year period. The paper considers the various factors that have shaped the surge of gold spot prices over the last two decades using quarterly data. The analysis considers the role of structural changes such as China’s liberalization of the domestic gold market post-2003 and its impact on demand as well as other important economic factors such as risk, the role of quantitative easing and other fundamental factors in the gold market. The study investigates which of the macroeconomic and structural factors are responsible for the long term bullish trend in the gold price, of which China, global economic risk assessments along with quantitative easing have been crucial to understanding the almost uninterrupted price increase over the period.